Utilization of kenaf core fiber – marine clay mixture as a landfill liner material - Diana Che Lat,; Siti Nur Aishah Mohd Noor,; Roslizayati Razali,; Husaini Rosli,; Noor Shazreen A. Rahman, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Nowadays, leachate production is a big concern and causes a serious hazard to the soil and groundwater which causes the subsurface soil to be polluted as a result of the loss of soil quality and environmental pollution. This study aims to study the potential of using kenaf core fiber and marine clay mixtures as improved landfill liner material. Relevant laboratory tests such as atterberg limit test, specific gravity test, and particle size distribution were performed to examine basic geotechnical properties of marine clay soil collected from Batu Kawan, Penang. Besides that, compaction test and hydraulic conductivity test were carried out for soil mixed with kenaf core fiber to determine the strength and permeability characteristics. The results found that the marine clay has significantly adequate physical properties to be used as a landfill liner. The permeability test for marine clay soil inclusion of kenaf core fibre indicated that the hydraulic conductivity of the samples admixture for 0%, 4%, 8%, and 12% ranged between 6.68 × 10-9 and 1.57 × 10-8 m/s. Compaction of marine clay mix kenaf core fibre samples resulted in maximum dry density, ρdmax that ranged between 0.936 and 1.595 g/cm3 and optimum moisture content, wopt that ranged between 19.8% and 24%. Hence the inclusion of kenaf core fiber in marine clay soil improves the maximum dry density value, decrease permeability of marine clay and could be potentially used for landfill liner material.